Tomato yellow leaf curl viruses: ménage à trois between the virus complex, the plant and the whitefly vector - DÍAZ‐PENDÓN, JUAN ANTONIO (Mol Plant Pathol, 2010)
Tomato yellow leaf curl disease (TYLCD) is one of the most devastating viral diseases affecting tomato crops in tropical, subtropical and temperate regions of the world. Here, we focus on the interactions through recombination between the different begomovirus species causing TYLCD, provide an overview of the interactions with the cellular genes involved in viral replication, and highlight recent progress on the relationships between these viruses and their vector, the whitefly Bemisia tabaci. Taxonomy:  The tomato yellow leaf curl virus‐like viruses (TYLCVs) are a complex of begomoviruses (family Geminiviridae, genus Begomovirus) including 10 accepted species: Tomato yellow leaf curl Axarquia virus (TYLCAxV), Tomato yellow leaf curl China virus (TYLCCNV), Tomato yellow leaf curl Guangdong virus (TYLCGuV), Tomato yellow leaf curl Indonesia virus (TYLCIDV), Tomato yellow leaf curl Kanchanaburi virus (TYLVKaV), Tomato yellow leaf curl Malaga virus (TYLCMalV), Tomato yellow leaf curl Mali virus (TYLCMLV), Tomato yellow leaf curl Sardinia virus (TYLCSV), Tomato yellow leaf curl Thailand virus (TYLCTHV), Tomato yellow leaf curl Vietnam virus (TYLCVNV) and Tomato yellow leaf curl virus(TYLCV). We follow the species demarcation criteria of the International Committee on Taxonomy of Viruses (ICTV), the most important of which is an 89% nucleotide identity threshold between full‐length DNA‐A component nucleotide sequences for begomovirus species. Strains of a species are defined by a 93% nucleotide identity threshold. Host range:  The primary host of TYLCVs is tomato (Solanum lycopersicum), but they can also naturally infect other crops [common bean (Phaseolus vulgaris), sweet pepper (Capsicum annuum), chilli pepper (C. chinense) and tobacco (Nicotiana tabacum)], a number of ornamentals [petunia (Petunia×hybrida) and lisianthus (Eustoma grandiflora)], as well as common weeds (Solanum nigrum and Datura stramonium). TYLCVs also infect the experimental host Nicotiana benthamiana. Disease symptoms:  Infected tomato plants are stunted or dwarfed, with leaflets rolled upwards and inwards; young leaves are slightly chlorotic; in recently infected plants, fruits might not be produced or, if produced, are small and unmarketable. In common bean, some TYLCVs produce the bean leaf crumple disease, with thickening, epinasty, crumpling, blade reduction and upward curling of leaves, as well as abnormal shoot proliferation and internode reduction; the very small leaves result in a bushy appearance.